Pemisahan Emas Pada Ram (Random Access Memory) Komputer : Pengaruh Variasi Rasio Jumlah Sampel : Volume Pelarut HNO3 Dan Jenis Presipitan - Restika Rahayu; Yusnimar Yusnimar; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Gold metal has been using in electronics and telecommunication industry, for example, computer RAM . The separation of gold from the computer's RAM has been done in this study. To get the maximum results in the separation of the gold used variations in the ratio of the number of samples : HNO3 solvent volume ( w/v 1:3 ; 1:6 ; 1:9 ) and the type of precipitant ( NaHSO3 and H2C2O4 ) . In this study, a certain number of samples is used computer RAM with a size of 1-3 mm then it is been leaching with HNO3 at a temperature of 70˚C for 1 hour. The precipitate formed is separated from the filtrate. The precipitate was dissolved in Aqua Regia at a temperature of 70˚C for 30 minutes further diluted with Aqua DM until the volume is 50 mL . Au concentration was analyzed by AAS Atomic Absorption Spectrophotometry and Au deposited with NaHSO3 and H2C2O4 . Based on the analysis result, the maximum Au concentration at the former computer RAM is equal to 54.95 ppm. For 5 grams of the sample , the maximum weight of Au precipitate obtained 0.72 grams by using H2C2O4 as a precipitant .Keyword : Au, RAM computer, Leaching, Precipitant